The Effectiveness Of Electronic Registration Of Mortgage Rights Electronically At The Land Office Bogor City - Riswanti, Gita; Bhudiman, Budy; Fajri, Ibrahim (JURNAL MAHASISWA YUSTISI, 2023)
The development of the current era of globalisation includes the field of technology, especially in the registration of Mortgage Rights, which used to be done manually and took a lot of time to register. Along with the development of technology and the application of e-Government applications, everything can be done electronically or online, and make registration easier and save a lot of time. One of these services is the electronic mortgage service (HT-el). However, the application of electronic Mortgage Rights will get obstacles at the beginning, especially regarding the knowledge of its users. The research method used is empirical juridical. Mortgage encumbrance must meet the requirements of speciality and publicity. The principle of speciality in granting HT must be fulfilled. The principle of speciality is a principle that requires that mortgage rights can only be imposed on specific land. The principle of speciality guarantees that it is in accordance with the identity of the parties, the place of residence, as well as the certainty of the amount of debt, the value of the mortgage and the object used as collateral along with the value of the mortgage in accordance with what is contained in the APHT. After the APHT is made, the PPAT is obliged to register it at the Land Office, even though it is not an interested party, by sending the relevant APHT along with other necessary documents. The registration is a form of fulfilment of the publicity requirement. The rules regarding this registration are stipulated in Article 13 and Regulation of the Minister of Agrarian Affairs/Head of BPN number 5/1996 and Letter of the Minister of Agrarian Affairs/Head of BPN dated 26 June 1996 number 630.1-1826. Since 8 October 1997, it has been regulated in Ministerial Regulation 3/1997. In its application, it is regulated in detail in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 5 of 2020 on Electronically Integrated Mortgage Services.